Wait a Second! How Delays Disrupt Optimal Policies - Sarah Dumnich; Britton Wolfe (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
Communication delays can lead to inconsistent views of the world among the different agents. We prove that an optimal policy in a system with instant communication can be suboptimal when the same system exhibits communication delay.